How low should we target the LDL goal to improve survival for acute coronary syndrome patients in Hong Kong?. Issue 1 (December 2015) - Lee, Vivian; Chau, Raymond; Cheung, Herich; Yu, Cheuk; Lam, Yat; Yan, Bryan
Abstract Background Utilization of lipid-lowering agents has been associated with improved long-term outcomes in acute coronary syndrome (ACS) patients. However, updated data regarding local use and outcomes was lacking. Methods We retrospectively reviewed 696 hospitalized patients in the local ACS registry of Prince of Wales Hospital during 1 January 2008 to 31 December 2009 with data retrieved using computerized clinical records of all patients. Results Among the 402 MI patients included, 104 (25.9 %) were not prescribed with statins at discharge. Percutaneous coronary intervention (PCI) not performed or planned during hospitalization (OR: 0.324, p  = 0.001) and latest lower LDL-C level before discharge (OR: 0.221 for an increment of 1 mmol/L, p  = 0.009) were significant independent predictors of the absence of statin prescriptions at discharge. A significantly lower all-cause mortality rate (14.4 % vs 51.7 %, p  < 0.001), fewer total hospitalizations (p  < 0.001) and fewer hospitalizations due to cardiovascular problems (p  < 0.001) were observed in patients discharged with statins. LDL-C goal attainment of < 2.6 mmol/L resulted in a significant reduction in mortality (10.8 % vs 24.2 %, p  = 0.001), but not for goal attainment of < 1.8 mmol/L. Significant difference in survival existed only when LDL-C cut-off values were above 2.4 mmol/L. Conclusions This study revealed the under-utilization of statin therapy in eligible MI patients at discharge and unsatisfactory percentages of LDL-C goal attainment, and also reassured the role of low LDL-C reduction to < 2.6 mmol/L in the management of MI. However, the current study did not show that the lower LDL-C reduction improved survival of ACS patients. Further research should be conducted to assess the necessity of aggressive LDL-C reduction to < 1.8 mmol/L in local patients.